Analysis of natural landing trajectories for passive landers in binary asteroids: A case study for (65803) 1996GT didymos - Çelik, Onur; Sánchez, Joan-Pau; Karatekin, Özgür; Ritter, Birgit (Cranfield University, 2017)
Binary asteroids are believed to constitute about 15% percent of the near-Earth asteroid (NEA) population. Their abundance and yet-to-be-resolved formation mechanism make them scientifically interesting, but they can also be exploited as a test bed for kinetic impactors, as the Asteroid Impact and Deflection Assessment (AIDA) joint mission proposal suggested. In addition to impactor spacecraft of AIDA, i.e. DART, the observation spacecraft, called Asteroid Impact Mission (AIM) (whose future is now uncertain) is to characterize Didymos, including pre- and post-impact variations. Due to the highly perturbed dynamical environment around asteroids, large, and generally expensive missions are preferred to be operated from a safe distance from target asteroid. Even if advanced remote sensing techniques provide the finest details of the target, surface agents can obtain higher resolution and ground truth data. Lander solutions for small body exploration have already been suggested in various missions/proposals. The most recent example is the AIM proposal, which envisage to deploy MASCOT lander on the surface of Didymoon. Additionally, AIM proposed to carry two CubeSats on board. A team led by Royal Observatory of Belgium (ROB) proposed Asteroid Geophysical Explorer (AGEX) CubeSat to land on Didymoon. CubeSats can be employed much more daringly in small body environments due to their versatile character and low development cost. Nevertheless, they possess only limited AOCS capabilities because of their size, and in most cases they are passive. This research offers novel landing trajectories by exploiting the natural dynamics of binary systems. The framework of Circular Restricted Three-Body Problem is used for this purpose, in which two asteroids orbit each other around their common center of mass, while third body (CubeSat) move under their gravitational field. Landing trajectories are propagated backwards in time; from each latitude-longitude points in densely meshed surface through the low energy gate at L2. A newly developed bisection algorithm ensures to generate the lowest energy trajectory for landing point under given constraints. The results suggest that landing speeds less than 8 cm/s are possible, while coefficient restitutions of over 0.9 for spherical asteroids would ensure a successful landing. Robustness of trajectories is also investigated. Uncertainties in deployment mechanism and GNC errors of mothership are considered. Trajectories that are obtained in backwards time propagation are added pseudo-random errors, then propagated forward to the surface in a Monte Carlo simulation, in which 1000 trajectories are propagated. The deployment altitude is found to be severely degrading the success rate. The GNC velocity errors are also found to be more effective than their position counterparts. The success rate over 99.7% (3) can be achieved, though extra requirements might need to be considered for mothership design.
Keywords: Binary asteroids; Didymos; Natural landing trajectories; CR3BP; CubeSat